PENGEMBANGAN STRATEGI PEMASARAN UNTUK PRODUK PERTANIAN LOKAL: PENDAMPINGAN DAN IMPLEMENTASI PADA PETANI DESA REMBANG KAB. KEDIRI - Laely, Nur; Widianto, Aris; Suwito, Eko (LP2M STP Mataram, 2024)
The community service activity entitled Development of Marketing Strategies for Local Agricultural Products: Assistance and Implementation for Farmers in Rembang Village, Kediri Regency, was carried out to improve farmers' knowledge and skills in digital marketing to expand market access and increase income. This program responds to major problems such as dependence on middlemen and low utilization of information technology. The methods used include initial surveys, preparation of training modules, digital marketing and product branding training, and intensive mentoring for three months. The results of the evaluation show that farmers have successfully adopted digital marketing technology, increased product competitiveness, and expanded the market beyond the Kediri area. In addition, there was a 20% increase in revenue after the training. Farmers' satisfaction with the program reached 90%, showing the relevance of the training material. This program provides practical solutions and can be a model of service applied in other regions with similar problems to improve the welfare of farmers sustainably